2014
DOI: 10.1261/rna.044792.114
|View full text |Cite
|
Sign up to set email alerts
|

The role of RNA structure at 5′ untranslated region in microRNA-mediated gene regulation

Abstract: Recent studies have suggested that the secondary structure of the 5 ′ untranslated region (5 ′ UTR) of messenger RNA (mRNA) is important for microRNA (miRNA)-mediated gene regulation in humans. mRNAs that are targeted by miRNA tend to have a higher degree of local secondary structure in their 5 ′ UTR; however, the general role of the 5 ′ UTR in miRNA-mediated gene regulation remains unknown. We systematically surveyed the secondary structure of 5 ′ UTRs in both plant and animal species and found a universal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 35 publications
0
76
1
2
Order By: Relevance
“…It already has been suggested that secondary structures or upstream open reading frames in the 59 UTR can play a role in mRNA degradation (Oliveira and McCarthy, 1995). The GC content of the 59 UTR and 59 UTR length can influence mRNA structure near the 59 cap, thus regulating posttranscriptional processes (Gu et al, 2014). In particular, the competition between the formation of the translation initiation complex and the degradation machinery at the 59 UTR has been shown to regulate the stability of various transcripts (de la Cruz et al, 2002;Dvir et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It already has been suggested that secondary structures or upstream open reading frames in the 59 UTR can play a role in mRNA degradation (Oliveira and McCarthy, 1995). The GC content of the 59 UTR and 59 UTR length can influence mRNA structure near the 59 cap, thus regulating posttranscriptional processes (Gu et al, 2014). In particular, the competition between the formation of the translation initiation complex and the degradation machinery at the 59 UTR has been shown to regulate the stability of various transcripts (de la Cruz et al, 2002;Dvir et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These elements are the 5′ UTR [69,70], the open reading frames (ORFs) [71,72] and the coding sequence (CDS) for mRNAs [73], which have been included in the search of certain miRNA target prediction tools. For example, the new version of DIANA microT (v5.0) includes the prediction of miRNA:MRE recognition in the CDS region [66].…”
Section: Biological Elements For Computational Analysismentioning
confidence: 99%
“…The mechanism(s) by which mRNA structure regulates gene expression comprise virtually any step of the gene expression process (Mortimer et al, 2014) including transcription (Frieda and Block, 2012), splicing (Warf and Berglund, 2010), stability (Ferre-D’Amare, 2011), and translation (Mauger et al, 2013, Mandal and Breaker, 2004). mRNA structure is also required for proper miRNA-mediated regulation (Meijer et al, 2013, Gu et al, 2014b), and mRNA cellular localization (Jambor et al, 2014, Martin and Ephrussi, 2009). Most significantly, it has been demonstrated that mRNA conformation governs the expression of their encoded proteins both in vitro (Wan et al, 2011, Kertesz et al, 2010) and in vivo , as indicated by genome-wide mRNA structural profiling (Ding et al, 2014).…”
Section: Mechanisms By Which Synonymous Mutations Contribute To Gene mentioning
confidence: 99%